Developing a tool to measure Employee wellbeing in Saudi work Environment (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to develop a tool to measure the multidimensional well-being of employees in Saudi work environment. It sought to identify and assess the psychological, emotional, professional, organizational, cultural, health, and environmental aspects of workplace well-being. The researcher designed the tool based on theoretical frameworks and previous studies, and ensured its validity and reliability through psychometric analysis.The tool consists of 20 items distributed across four dimensions: psychological and emotional, professional and functional, organizational and cultural, and health and environmental. It was applied to a pilot sample of 150 employees, followed by a final sample of 700 employees across various sectors. The results confirmed the high internal consistency and reliability of the tool using Cronbach’s Alpha, Omega, and split-half methods. The items demonstrated significant correlations at the (0.01) level with their respective dimensions and with the total score of the scale.Based on these findings, the study recommends adopting this tool as a standardized local measure to assess employee well-being in the Saudi workplace, and to support institutional efforts aimed at enhancing employee satisfaction and productivity.
Keywords: Employee Wellbeing; Workplace Environment; Occupational Health; Psychological Wellness